Feminist Representation of Nyai Ontosoroh in the Film Bumi Manusia: A Critical Discourse Analysis Based on Sara Mills - Dina Sudarmika; Abdul Haris; Safrudiningsih Safrudiningsih; Hillary R. Amanda (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2026)
The film Bumi Manusia, adapted from Pramoedya Ananta Toer’s novel and released in 2019, portrays women through gender roles within indigenous, Indo, and Dutch communities during the Dutch colonial period. Women in the film are frequently depicted as weak and oppressed, reflecting the patriarchal culture of the time. Audience engagement with the film produces diverse interpretations, as viewers respond to how the story communicates women’s social positions and roles. This study uses a qualitative descriptive approach to examine feminist representations in the film. Data were collected through documentation, including quotes and visual elements from key scenes that highlight feminist themes. Detailed observation and analysis of the film were conducted to gain deeper insights. Critical discourse analysis, based on Sara Mills’ theory, was applied to understand feminist discourse in visual and textual media. The findings describe feminist values from the perspectives of subject, object, and reader positions. The film demonstrates liberal feminist ideology through women’s struggle and resistance against oppressive gender roles. It also challenges discrimination and advocates for the fulfillment of rights and opportunities for all individuals, including women. Bumi Manusia illustrates how media narratives can reveal, critique, and negotiate gender inequality within historical and cultural contexts.